Why are capital income taxes so high? - Martin Flodén (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
The Ramsey optimal taxation theory implies that the tax rate on capital income should be zero in the long run. This result holds even if the social planner only cares about workers that do not hold assets, or if the planner only cares about any other group in the economy. This paper demonstrates that although all households agree that capital income taxation should be eliminated in the long run, they do not agree on how to eliminate these taxes. Wealthy households would prefer a reform that is funded mostly by higher taxes on labor income while households with little wealth would prefer a reform that is funded mostly by high taxes on initial wealth. Pareto improving reforms typically exist, but the welfare gains of such reforms are modest.
Keywords: E60; H21; 330; optimal taxation; inequality; redistribution; Optimale Besteuerung; Kapitalertragsteuer; Einkommensumverteilung; Vermögen; Steuerpolitik; Theorie